(untitled) (Bangladesh Journal of Pharmacology, 2015)
The objective of the study was to evaluate anti-ulcer potential of Mentha longifolia. The rats (four groups) were given orally the vehicle (normal saline, 2 mL/kg) as control group, ethanol extracts of the plant at dose of 100 mg/kg and 200 mg/kg of body weight and ranitidine (20 mg/kg) as standard drug (positive control). Ulcer was induced by oral administration of alcohol (80%) and aspirin (200 mg/kg). The gastric tissues were examined to determine ulcer index and percentage protection. Histopathological evaluation was also performed to support the results. Ethanol extract of M. longifolia showed reduction in ulcer index (p<0.05). Treatment with ethanolic extract of M. longifolia at dose of 100 mg/kg and 200 mg/kg of body weight gave ulcer protection (30.5 ± 4.5%) and (47.1 ± 5.9%) respectively. In conclusion, ethanolic extract of M. longifolia has anti-ulcer activity.